Analisis Nilai Tambah Pengolahan Abon Ikan Tuna di Kelurahan Mata Kecamatan Kendari Kota Kendari (Studi Kasus Industri Rumah Tangga Dzakiyah Permata) - Dzulmawan, Muhammad; Geo, Laode; Gafaruddin, Abdul (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
The purpose of this research is to analyze the amount of profit and value added that resulted in the processing of tuna fish abon in the household industry "Dzakiyah Permata Kendari" in Kelurahan Mata. Sample determination is done intentionally. The analytical method used is value-added analysis using Hayami method. The results showed that the added value created from the processing of abon fish creates added value of Rp 184,485 / kg value-added ratio to the value of the product of 89.8% and profit Rp 163.353 / kg with the profit rate of 88.5%.